Multi-objective design optimization strategies for small-scale vertical-axis wind turbines - Posteljnik, Zorana; Stupar, Slobodan; Svorcan, Jelena; Peković, Ognjen; Ivanov, Toni (Structural and multidisciplinary optimization, 2016)
Extracting energy from wind has been an interesting and serious topic over the last few decades and a lot of work has been done on the subject. This paper discusses in detail possible approaches to optimization of a somewhat less known type of wind turbines, particularly suitable for small consumers. In order to perform full aerodynamic and structural shape optimization of a small-scale vertical-axis wind turbine, a Double-multiple streamtube model code, known to provide good results in stationary working regimes, was complemented by a finite element analysis and implemented into a multi-objective particle swarm algorithm. For the purpose of shortening the total time needed for aerodynamic computation, the performed numerical simulations were two-dimensional and experimentally measured static airfoil data were used. The used aerodynamic model was validated against the available experimental data of similar wind turbines. The subsequent structural analyses of the composite turbine blades were performed by applying computed maximal aerodynamic forces together with gravitational and inertial loads. By employing various input and output parameters different multi-objective optimization strategies were analyzed and compared and their applicability was demonstrated. Investigated input parameters included: wind turbine rotor diameter, blade length, chord and airfoil, composite shell thickness, laminate lay-up and ply orientations, while optimization goal functions and constraints comprised rated power, cut-in and optimal wind speed, blade mass, tip deflection, failure index and blade natural frequencies. The fidelity and accuracy of proposed methodologies can be increased by employing more complex numerical models which can easily be implemented into the code.